Nutritional Status, Health Status, and Work Productivity of Cocoa Farmers in Polewali Mandar, Indonesia - Yunieswati, Wilda; Marliyati, Sri Anna; Setiawan, Budi (Jurnal Gizi dan Pangan, 2020)
The objective of this study was to analyze the associations between nutritional status, health status, other determining factors with work productivity of cocoa farmers. This cross-sectional study involved 58 male cocoa farmers aged 18–65 years old in two districts of Polewali Mandar. Data on food consumption and habit as well as health status were collected via structured interviews. While, blood pressure and anthropometric parameters were measured using standard equipment of blood pressure meter, weight scale, and height scale. Spearman’s test and Principal Components Regression (PCR) analysis were implemented to explore factors associated with farmers’ work productivity. There was no relationship between Body Mass Index (BMI) and work productivity. However, there was a significant positive association between central obesity with days of absent (r=0.275; p=0.037). We also found negativeassociation between blood pressure and the amount of cocoa picked daily (r=-0.366; p=0.005). PCR statistical analysis results showed that the amount of cocoa picked per day were significantly associated with smaller waist circumference, coffee consumption, and good exercise habit. While, decrease in consumption of fruits and vegetables was significantly associated with the number of absence days due to health problems. Thus, it can be concluded that work productivity of male cocoa farmers was associated with food consumption, physical activity, and lifestyle factors.